Color Pattern Steganography in Images - Mohammed Zaki, Hassan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Text steganography into images is one of the important strategies that are used to hide the transmitted secret messages via internet connections. Most of the proposed methods required mapping key to recover the hidden secret messages and implement more complex algorithms in hiding and recovering processes. The paper proposed an improved method to hide text in image cove based on the color pattern of the cover image. It based on the sequence of the new occurrence of the color. The results showed that the proposed method has high performance in hiding with extremely low PSNR(<0.002). The low differences between the original image and the stegno image provide more secured hiding that satisfied the State-of-Art. The proposed method can be used in transmitting classified and confidential messages via public internet connections.